The effect of technology stress on knowledge concealment with the mediating role of job fatigue and moderating work autonomy - Hossein Jamali; Mehdi Kabirinaeini; Zeynab Elahi (مدیریت راهبردی دانش سازمانی, 2025)
Purpose: Technology-induced stress can be a significant factor in reducing the effectiveness of knowledge management in work environments. Pressures from new technologies, such as the need for continuous adaptation to rapid changes, the complexity of digital tools, and the increasing volume of processed information, may lead to job burnout, reduced individual focus, and ultimately, a decreased willingness of employees to share knowledge. In such situations, employees may have a greater tendency to conceal their tacit knowledge due to stress and work pressures, which can negatively impact organizational productivity and reduce access to knowledge repositories and the organization's ability to leverage explicit and tacit knowledge. This issue can ultimately limit organizations' ability to create effective communities of practice and organizational learning. Therefore, the present study aims to investigate the effect of technology stress on knowledge hiding, and in this regard, the mediating role of job burnout and the moderating role of job autonomy are evaluated. Examining these factors can lead to a deeper understanding of how technology affects employees' knowledge-based behaviors and provide solutions for better stress management and improved knowledge interactions in organizations.Methodology: This study is descriptive-survey and examines the effects of technology-induced stress on knowledge hiding in the workplace. The statistical population of this research consisted of 250 employees of Saman Electronic Payment Company. To determine the sample size, Cochran's formula was used, based on which 150 people were selected as the statistical sample. This sample was randomly selected from among the organization's employees to ensure the generalizability of the research results to the larger population. The tools used in this research included four standard questionnaires that respectively assessed technology stress, knowledge hiding, job burnout, and job autonomy. To measure the reliability of these questionnaires, Cronbach's alpha coefficient was used. The results showed that the reliability for the technology stress questionnaire was 0.746, for the job autonomy questionnaire 0.561, for the job burnout questionnaire 0.714, and for the knowledge hiding questionnaire 0.837. These values indicate acceptable reliability of the research tools and contribute to the validity of the research results. In addition, the validity of the questionnaires was examined using the average variance extracted method, and the results showed that the construct validity was confirmed. Also, the Fornell-Larcker method was used to evaluate convergent and discriminant validity, and the results of this method also confirmed the appropriate validity of the research tools.Results: The results of statistical inference showed that technology stress has a significant impact on knowledge hiding and job burnout among employees. Job burnout had a significant impact on knowledge hiding among employees. The mediating role of job burnout was confirmed, but the moderating role of job autonomy was rejected.Conclusion: The research results showed that technology-induced stress indirectly reduces the willingness to share knowledge among employees by increasing job burnout. Pressures from new technologies and their complexities can create stress in the workplace, which leads to job burnout. This job burnout, in turn, prevents employees from actively participating in knowledge-sharing processes, as they feel unable to manage these pressures and interact with complex systems. This process will ultimately negatively impact team and organizational performance and reduce the effectiveness of teamwork. Additionally, job autonomy has been introduced as a moderating factor that can reduce the negative effects of technology stress and job burnout. In other words, when employees have more freedom in choosing how to perform their tasks and feel more control over their work environment, they experience less stress and their job burnout decreases. The results show that creating conditions that strengthen job autonomy in the organizational environment can reduce stress and job burnout. Furthermore, this may increase employees' motivation to share knowledge and ultimately help improve overall organizational performance, although these effects will vary depending on different environmental and organizational conditions.Originality/Value: It is essential that the managers of Saman Electronic Payment Company develop and implement comprehensive and well-structured programs to increase job autonomy and personal control of employees in the workplace. These programs can include creating flexible work structures that allow employees to choose how to perform their tasks according to their work style and personal abilities. Flexibility in work scheduling, the possibility of remote work, and delegation of authority in daily task-related decisions are among the solutions that can give employees a greater sense of control and, as a result, reduce the level of stress and job burnout. Also, providing rewards and incentives for independent and creative performance can lead to increased employee productivity and strengthen their sense of responsibility.In addition, the use of efficient and simple technologies that do not require complex and time-consuming interactions with difficult systems can play an important role in reducing technology-induced stress. Using user-friendly software, optimizing organizational processes, and providing the necessary training to effectively use these tools can help employees increase their productivity and reduce unnecessary pressures from complex technologies. Conducting training courses in stress management and optimal use of new technologies is also an important step in empowering employees. These measures not only reduce job burnout and increase the motivation to share knowledge among employees but also help improve overall organizational performance, increase team interactions, and promote organizational culture.